BRAND AWARENESS MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Upadana, Made wahyu Krisna; Pramudana, Komang Agus Satria (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p14, 2020)
In order to stay in competition, Starbucks Coffee must be able to develop and innovate to determine an effective strategy. One of them is by using attractive social media marketing to builds brand awareness and leading to consumer purchasing decisions. The research objective is to determine the role of brand awareness mediating the effect of social media marketing on purchasing decisions. This research was conducted in Denpasar with 110 respondents through a purposive sampling method. Data collected through questionnaires and analyzed by path analysis. Based on the results, social media marketing has apositive and significant effect on purchasing decisions. This shows that the better the use of social media marketing, the more purchasing decisions from consumers. Brand awareness positively and significantly mediates the relationship between social media marketing and purchasing decisions. Brand awareness is able to mediate the relationship of social media marketing to purchasing decisions Keywords: social media marketing, brand awareness, purchasing decisions